Implications of improved representations of plant respiration in a changing climate. Issue 1 (December 2017) - Huntingford, Chris; Atkin, Owen; Martinez-de la Torre, Alberto; Mercado, Lina; Heskel, Mary; Harper, Anna; Bloomfield, Keith; O'Sullivan, Odhran; Reich, Peter; Wythers, Kirk; Butler, Ethan; Chen, Ming; et al.
Abstract Land-atmosphere exchanges influence atmospheric CO2 . Emphasis has been on describing photosynthetic CO2 uptake, but less on respiration losses. New global datasets describe upper canopy dark respiration (R d ) and temperature dependencies. This allows characterisation of baselineR d, instantaneous temperature responses and longer-term thermal acclimation effects. Here we show the global implications of these parameterisations with a global gridded land model. This model aggregatesR d to whole-plant respirationR p, driven with meteorological forcings spanning uncertainty across climate change models. For pre-industrial estimates, new baselineR d increasesR p and especially in the tropics. Compared to new baseline, revised instantaneous response decreasesR p for mid-latitudes, while acclimation lowers this for the tropics with increases elsewhere. Under global warming, newR d estimates amplify modelled respiration increases, although partially lowered by acclimation. Future measurements will refine howR d aggregates to whole-plant respiration. Our analysis suggestsR p could be around 30% higher than existing estimates. New global datasets of upper canopy vegetation respiration have become available and their impact on global carbon cycle models is unclear. Here, the authors show the implications of these parameterisations with a global gridded land model and report significantly higher global plant respiration estimates.